2004
DOI: 10.1111/j.1365-4632.2004.02169.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous necrosis by calcific uremic arteriolopathy

Abstract: Background Calcific uremic arteriolopathy is a rare and serious disorder characterized by systemic medial calcification of the arteries and tissue ischemia. Most often it is found in patients with chronic renal failure on dialysis and in renal transplant recipients with secondary hyperparathyroidism. MethodsWe report six patients with end-stage renal disease [five on hemodialysis (one with a nonfunctioning renal graft) and one on peritoneal dialysis] who developed painful livedo reticularis and skin necrosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…35 Calciphylaxis has a high associated morbidity and can result in fatality in up to 80% of cases. 32,35 Cryoglobulinemia. Cryoglobulins are cold-insoluble B-cellederived immunoglobulins (and/or complement) that aggregate and precipitate at temperatures below 378C in vivo or in vitro.…”
Section: Histopathologymentioning
confidence: 99%
See 2 more Smart Citations
“…35 Calciphylaxis has a high associated morbidity and can result in fatality in up to 80% of cases. 32,35 Cryoglobulinemia. Cryoglobulins are cold-insoluble B-cellederived immunoglobulins (and/or complement) that aggregate and precipitate at temperatures below 378C in vivo or in vitro.…”
Section: Histopathologymentioning
confidence: 99%
“…[33][34][35] The disorder most often involves the lower extremities. 32 Internal derangements of calcium-phosphate metabolism and of the regulatory factors derived from vascular smooth muscle cells including osteopontin, osteoprotegerin, and matrix alpha-carboxyglutamic acid protein, have been implicated in the pathogenesis of this disorder. 35 Although vascular calcifications occur frequently in patients with hemodialysis, progression to tissue ischemia is rare.…”
Section: Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…14,19-21 Urgent parathyroidectomy might be necessary if there is elevated parathyroid hormone level. 22,23 Sodium thiosulfate reduces metastatic tissue calcification, acts as an antioxidant, and induces endothelial nitric oxide synthesis, which improves blood flow and tissue oxygenation leading to ulcer healing. 24,25 Bisphosphonates, both …”
Section: Discussionmentioning
confidence: 99%
“…An earlier review of the literature found 39 cases of calciphylaxis in which protein C levels were reported, and 22 cases with reported levels of protein S. 2 The cases included patients with and without renal disease, although the majority of patients had end-stage renal disease. In this review, 36% had decreased protein C levels, and 50% had decreased levels of protein S. We performed a similar review of the more recent literature and found an additional 22 cases of patients with calciphylaxis and reported protein C levels and 18 with levels of protein S. [2][3][4][5][6][7][8][11][12][13]15,[17][18][19][20][21][22] Combining the two literature reviews shows that 38% had decreased protein C levels and 43% had decreased levels of protein S.…”
mentioning
confidence: 93%